Persons with cancer diagnosis as victims/survivors: Patterns of victimization, empowering support and posttraumatic growth - Nikolić-Ristanović Vesna (Temida)
The paper deals with the analyses of primary and secondary victimisation patterns to which cancer diagnosed persons are exposed, as well as an analyses of their needs and the adequacy of the support they receive from persons from their close surrounding, from professionals as well as from state institutions and nongovernmental organizations. The main aim of the paper is to examine applicability of basic victimological concepts such as the notion of victim-survivor, victimization, victim needs, agency v. passivity, self help, social support, posttraumatic disorder/ growth, to the experiences of persons with cancer diagnosis. Consequently the experiences of persons with cancer diagnosis are compared with the experiences of crime victims. On the basis of this analyses, recommendations regarding the possible exchange of experiences and unification of knowledge about crime victims’ and cancer diagnosed persons’ needs, as the basis for the improvement of existing and the development of new mechanisms of support and (self) help beneficial for both groups are presented. [Projekat Ministarstva nauke Republike Srbije, br. 179044: Razvoj metodologije evidentiranja kriminaliteta kao osnova kreiranja efikasnih mera za njegovo suzbijanje i prevenciju]